Optimal inflation with corporate taxation and financial constraints - Daria Finocchiaro; Giovanni Lombardo; Caterina Mendicino; Philippe Weil (Sveriges Riksbank, 2015)
This paper revisits the equilibrium and welfare effects of long-run inflation in the presence of distortionary taxes and financial constraints. Expected inflation interacts with corporate taxation through the deductibility of i) capital expenditures at historical value and ii) interest payments on debt. Through the first channel, inflation increases firms' taxable profits and further distorts their investment decisions. Through the second, expected inflation affects the effective real interest rate negatively, relaxes firms' financial constraints and stimulates investment. We show that, in the presence of collateralized debt, the second effect dominates. Therefore, in contrast to earlier literature, we find that when the tax code creates an advantage of debt financing, a positive rate of long-run inflation is beneficial in terms of welfare as it mitigates the financial distortion and spurs capital accumulation.
Keywords: E31; E43; E44; E52; G32; 330; optimal monetary policy; Friedman rule; credit frictions; tax benefits of debt